Gone With the Plague: Negotiating Sexual Citizenship in Crisis - Nielsen, Ken (Nordic Theatre Studies, 2018)
This article suggests that two historical performances by the Danish subcultural theatre group Buddha og Bagbordsindianerne should be understood not simply as underground, amateur cabarets, but rather that they should be theorized as creating a critical temporality, as theorized by David Román. As such, they function to complicate the past and the present in rejecting a discourse of decency and embracing a queerer, more radical sense of citizenship. In other words, conceptualizing these performances as critical temporalities allows us not only to understand two particular theatrical performances of gay male identity and AIDS in Copenhagen in the late 1980s, but also to theorize more deeply embedded tensions between queer identities, temporality, and citizenship. Furthermore, by reading these performances and other performances like them as critical temporalities we reject the willful blindness of traditional theatre histories and make a more radical theatre history possible.